Bank Marketing Mix Impact On Syrian Private Traditional Commercial Banks’ Profitability - العمار رضوان; عبيده هبة (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This paper aimed to discuss whether bank marketing mix affect the profitability of traditional private commercial banks operating in Syria during the period 2010 - 2017. Where the effect of the following independent variables has been studied: the number of banking services, the price of traditional services, the price of modern services, distribution, promotion, pepole, process and physical evidence, on the rate of return on equity as a dependent variable. The study adopted the Panel Data, which were collected from the financial reports of the studied banks, then the models of these data were estimated and the comparison between them was done on the basis of the restricted F test, where it was found that the fixed effects model is the most appropriate model for the study. The study concluded that there was no statistically significant effect of any of the elements of the marketing mix on the rate of return on equity of the studied banks, in other words, the banking marketing mix had no significant impact on the profitability of these banks during the period studied.